Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-59002
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Performance of Converging-Slot Holes With Different Exit-Entry Area Ratios

Abstract: Film cooling performances of two kinds of converging slot-hole (console) with different exit-entry area ratios have been measured using a new transient liquid crystal measurement technique which can process the nonuniform initial wall temperature. Four momentum ratios are tested. The film cooling effectiveness distribution features are similar for the two consoles under all the momentum ratios. Consoles with smaller exit-entry area ratio produce higher cooling effectiveness. And the laterally averaged cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The console film hole yielded less aerodynamic loss when compared to the circular and the fan shaped holes, but it showed higher thermal stress concentrations, particularly at the exit area. Liu et al [17] investigated the effect of exit-entry area ratios of 0.67 and 1.33 for console film hole on the film cooling performance. They noted that smaller exit-entry area ratio produced a better thermal protection due to higher film cooling effectiveness with minimum discharge coefficient.…”
Section: Adiabatic Film Coolingmentioning
confidence: 99%
“…The console film hole yielded less aerodynamic loss when compared to the circular and the fan shaped holes, but it showed higher thermal stress concentrations, particularly at the exit area. Liu et al [17] investigated the effect of exit-entry area ratios of 0.67 and 1.33 for console film hole on the film cooling performance. They noted that smaller exit-entry area ratio produced a better thermal protection due to higher film cooling effectiveness with minimum discharge coefficient.…”
Section: Adiabatic Film Coolingmentioning
confidence: 99%
“…The main hot gas velocity and coolant velocity are V g = 59 m/s and V c = 40 m/s respectively while from a previous validation study the temperature ratio was T c /T g =0. 6.…”
Section: Boundary Conditions and Computational Methodsmentioning
confidence: 95%
“…Liu et al [6] experimentally investigated two kinds of converging slot-holes with different exit-entry area ratios. The experiment was performed on a flat plate using transient liquid crystal measurement technique.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed flow structures of console film cooling flow field were also investigated by Azzi and Jubran [17] and Yao et al [18] through numerical simulations. Liu et al [19,20] further investigated the effect of console geometry variants including exit-entry area ratio and divergence angle on the film cooling performance of the consoles. The investigations showed that properly changing the geometry parameters of the console could improve the film cooling performance.…”
Section: Introductionmentioning
confidence: 99%